Impact of Subclinical Hypothyroidism on Cardiometabolic Biomarkers in Women - Harada, Paulo H. N. (J Endocr Soc, 2017)
CONTEXT: Whether subclinical hypothyroidism (SCH) is associated with cardiometabolic abnormalities is uncertain. OBJECTIVE: To examine diverse cardiometabolic biomarkers across euthyroid, SCH, and overt hypothyroidism (HT) in women free of cardiovascular disease. DESIGN: Cross-sectional adjusted associations for lipids, lipoprotein subclasses, lipoprotein insulin resistance score, inflammatory, coagulation, and glycemic biomarkers by analysis of covariance for thyroid categories or thyroid stimulating hormone (TSH) quintiles on a Women’s Health Study subcohort. SETTING: Outpatient. PATIENTS OR OTHER PARTICIPANTS: Randomly sampled 3914 middle-aged and older women for thyroid function analysis (TSH, free T4), of whom 3321 were not on lipid-lowering therapy. INTERVENTION: None. MAIN OUTCOME MEASURE: Associations of SCH and HT with cardiometabolic markers. RESULTS: Going from euthyroid to HT, the lipoprotein subclass profiles were indicative of insulin resistance (respective values and P for trend): larger very-low-density lipoprotein size (nm) (51.5 [95% confidence interval (CI), 51.2, 51.8] to 52.9 [51.8, 54.1], P = 0.001); higher low-density lipoprotein (LDL) particle concentration (nmol/L) [1283 (95% CI, 1267, 1299) to 1358 (1298, 1418), P = 0.004], and smaller LDL size. There was worsening lipoprotein insulin resistance score from euthyroid (49.2; 95% CI, 48.3, 50.2) to SCH (52.1; 95% CI, 50.1, 54.0) and HT (52.1; 95% CI, 48.6, 55.6); P for trend of 0.008. Of the other biomarkers, SCH and HT were associated with higher high-sensitivity C-reactive protein and hemoglobin A1c. For increasing TSH quintiles, results were overall similar. CONCLUSIONS: In apparently healthy women, SCH cardiometabolic profiles indicated worsening insulin resistance and higher cardiovascular disease risk markers compared with euthyroid individuals, despite similar LDL and total cholesterol. These findings suggest that cardiometabolic risk may increase early in the progression toward SCH and overt HT.